Analysis of Blood Flow Through the Pathologically Changed Main Artery - Rudiak, Alina; Słowiński, Jakub; Zawiślak, Maciej (Proceedings of the 13th International Scientific Conference, 2017)
During the examination a Computational Fluid Dynamics (CFD) analysis of blood flow through the physiological and pathologically changed aorta was performed. The model used in the Fluid—Structure Interaction analysis (FSI) has been enriched by a variable thickness of the wall in the section being subject to lesions. The influence of the occurrence of pathological change in the descending section of the thoracic aorta on the nature of blood flow, the value of flow parameters of fluid and endurance parameters of the wall of an arterial vessel, was demonstrated.